Investigation into the efficiencies of European football clubs with bi-objective multi-criteria data envelopment analysis - Arsu, Talip (Decision Making: Applications in Management and Engineering, 2021)
A financially successful football club can achieve sporting achievements as well as become financially stable. From this point of view, in this study, the efficiencies of clubs were investigated with the Bi-Objective Multi-Criteria Data Envelopment Analysis (BiO-MCDEA) model by using financial and sporting data of the 2015-2016, 2016-2017 and 2017-2018 seasons of 10 football clubs in the Big-Five League which is the locomotive of the football industry. In the study, the number of social media followers, the average number of viewers and total market value were used as input, and the UEFA club score and total revenues were used as output. As a result, Arsenal, Paris Saint-Germain, and Juventus were determined as efficient in the 2015-2016 season, Paris Saint-Germain and Liverpool in the 2016-2017 season, Manchester United, Paris Saint-Germain and Chelsea in the 2016-2017 season. The reasons as to why Paris Saint-Germain was efficient in all three seasons were also examined. In addition, in the sensitivity analysis conducted to determine the effect of inputs and outputs on the model, it was concluded that efficiency was highly related to financial data.